LAW ENFORCEMENT PROBLEM OF LOCAL GOVERNMENT ORGANIZATIONS IN ELDER CARE - Khongwan, Sonthon; Poon-eiad, Sittipan (Rangsit Journal of Law and Society, 2022)
Elderly are those who are in age of physical and mental change. There has been an increase in elderly population. Nursing the people in this age group is thus important. Recently, there exist the decentralization of power from the central government to local government organizations, assignment of power and duties to locality for public service systematization relating to elderly nursing for social work, and elderly’s quality of life improvement. An operation of local government organizations has to have an important instrument which is law used to nurse local elderly. This paper aims to study legal problems in elder care by local administrative organization, which have close relationships with the elderly. The data collected from legal document information in relation to issue in question is analyzed with descriptive analysis using content analysis technique. When the executives of the local administrative organization are in those localities, they will know the problems of the local elderly well. In addition, the law associating with decentralization of power from the central government to local administrative organization determines power and duties to locality for public service systematization relating to elderly’s social work and quality of life improvement. An operation of local administrative organization has to have an important instrument which is law used to improve local elderly’s quality of life. However, the study found that local administrative organization encounter problems of some law enforcement affecting operational efficiency associating with elderly’s quality of life promoting, including problem of a lack of specific law to elder care of local administrative organization, inequality of caregiving to elderly by local administrative organization, and improper participation of elderly and local administrative organization to elder care. These abovementioned legal problems demote law enforcement of local government organizations to elder care. For this reason, if there are law amendments to comply with the operational context relating to elderly by local administrative organization, elderly’s quality of life promotion will be appropriate and sustainable.